Muscle and Hip Contact Forces in Asymptomatic Men With Cam Morphology During Deep Squat - Catelli, Danilo S.; Kowalski, Erik; Beaulé, Paul E.; Lamontagne, Mario (Frontiers in Sports and Active Living, 2021)
Cam-morphology is defined as an aspherical femoral head-neck junction that causes abnormal contact of the acetabular rim with anterior hip. Cam imaging confirmation associated with clinical signs and hip in the hip or groin is characterized as femoroacetabular impingement syndrome. Although some individuals with cam morphology do not experience any symptoms, sparse studies have been done on these individuals. Understanding the way asymptomatic individuals generate muscle forces may help to explain the progression of the degenerative femoroacetabular impingement process and discover ways in preventing onset/worsening of symptoms. The purpose was to compare the muscle and hip contact forces of asymptomatic cam morphology (ACM) and femoroacetabular impingement syndrome (FAI) males compared to cam-free healthy male controls during a deep squat task. This prospective study compared 39 participants, with 13 in each group (ACM, FAI, and control). Five deep squatting trials were performed at a self-selected pace while joint trajectories and ground reaction forces were recorded. Generic model was scaled for each participant, and inverse kinematics and inverse dynamics calculated joint angles and moments, respectively. Muscle and hip contact forces were estimated using static optimization. All variables were time normalized in percentage by the total squat cycle and both muscle forces and hip contact forces were normalized by body-weight. Statistical non-parametric mapping analyses were used to compare the groups. ACM showed increased pelvic tilt and hip flexion angles compared to the FAI during the descent and ascent phases of the squat cycle. Muscle forces were greater in the ACM and control, compared to the FAI for the psoas and semimembranosus muscles. Biceps femoris muscle force was lower in the ACM compared to the FAI. The FAI had lower posterior hip contact force compared to both the control and ACM. Muscle contraction strategy was different in FAI compared to the ACM and control, which caused different muscle force applications during hip extension. These results rebut the concept that mobility restrictions are solely caused by the presence of the cam morphology and propose evidence that symptoms and muscle contraction strategy can be the origin of mobility restriction in male patients with femoroacetabular impingement syndrome.